PIRATES VS. THE BENGALI BOYS: A STUDY OF THE CONFRONTATION UPON THE OCEANIC SPACES IN THREE EARLY 20TH CENTURY BENGALI ADVENTURE NOVELS - Bhattacharjee, Prama (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the first half of the twentieth century, the Bengali literature reflected abundance of support from the educated middle class towards the rising militant nationalism and the attempts of refashioning of the Bengali masculinity. This was a prominent feature particularly found in the children’s adventure fiction of the time. Within the premises of this genre, the young male Bengali protagonists were deliberately exposed to various sorts of hardships out in the world in which they exhibited exemplary courage and determination before returning victorious to their own turf. The plotline involved adversities that were relatable yet exotic in the Bengali life under a colonial rule. The Bengali boy heroes explored all the three realms: the unknown forests of Africa or the far North East India including the Myanmar, the aerial domains, and the faraway seas and oceans. This essay closely inspects three major Bengali novels in this genre to find out a pattern of performative Bengali masculinity against the pirates in the watery spaces of the Indian Ocean and the Bay of Bengal, which was historically a place of perils during the early colonial rules.